2007
DOI: 10.1103/physrevlett.98.177403
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Phonon Bottleneck for Holes in Semiconductor Quantum Dots

Abstract: Size dependent hole dynamics are measured in colloidal CdSe quantum dots for a specific state-to-state excitonic transition. These experiments show that the hole energy loss rate increases for smaller quantum dots, contradicting known relaxation mechanisms for holes. These experiments reveal a new mechanism for hole relaxation in colloidal quantum dots which circumvents the expected phonon bottleneck for holes. The data are consistent with a nonadiabatic surface channel as the dominant pathway for hole relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
346
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(382 citation statements)
references
References 32 publications
32
346
4
Order By: Relevance
“…16 Understanding of surface processes is also important for controlling carrier multiplication (CM), a process in which two or more electronÀhole pairs are generated from a single absorbed photon, promising higher efficiency of QD-based solar cells than is currently possible. 17 Recent time-resolved experiments have demonstrated that radiative quantum yield, 18À20 exciton lifetime, 21 relaxation rates, 19,22,23 and the efficiency of the CM 24 are strongly affected by the type of ligands passivating the QD surface. Various contradicting data on CM efficiency reported in recent literature 25À28 may also be a result of uncontrolled differences in QD surface structure and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…16 Understanding of surface processes is also important for controlling carrier multiplication (CM), a process in which two or more electronÀhole pairs are generated from a single absorbed photon, promising higher efficiency of QD-based solar cells than is currently possible. 17 Recent time-resolved experiments have demonstrated that radiative quantum yield, 18À20 exciton lifetime, 21 relaxation rates, 19,22,23 and the efficiency of the CM 24 are strongly affected by the type of ligands passivating the QD surface. Various contradicting data on CM efficiency reported in recent literature 25À28 may also be a result of uncontrolled differences in QD surface structure and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The excited hole can then relax efficiently within the densely spaced valance band levels. 41 Figure 3BII and CII). In the non-adiabatic limit, the total ET rate is the sum of Auger-assisted ET rates to these product states, which is given by:…”
mentioning
confidence: 99%
“…8,9 In particular, hot electrons could relax rapidly by transferring energy to holes, which often have a greater effective mass and thus smaller energy spacing, through Auger-like processes followed by phonon-assisted relaxation 10,11 or nonadiabatic channels involving surface ligands. 12,13 Trap states 14,15 in the quantum dots and highfrequency vibrational modes in surface ligands 16 provide additional relaxation pathways to promote rapid carrier cooling. It has been demonstrated that by carefully designing multiple layers of heterostructures around colloidal CdSe quantum dots and suppressing these pathways, the lifetimes of hot carriers could be increased by 3 orders of magnitude up to 1 ns.…”
mentioning
confidence: 99%